Die gesundheitsökonomische Evaluation der GLICEMIA 2.0-Studie als Beispiel für eine komplexe Intervention - Forster, Cordula; Prax, Katja; Jaensch, Peter; Müller, Sebastian; Hepp, Tobias; Schlager, Helmut; Friedland, Kristina; Zerth, Jürgen (Gesundheitswesen, 2022)
BACKGROUND: A piggyback approach was used to evaluate the cost-effectiveness of the prevention program delivered at the point of care pharmacy in the GLICEMIA 2.0 study that sought to guide participants in the intervention group to improved glycemic control in type 2 diabetes with sustained incentivization of lifestyle changes, therapeutic compliance, and adherence. The control group received passive medication management and monitoring. METHODS: Primary endpoint of the GLICEMIA 2.0 study was the stabilization of HbA1c values. For health economic evaluation, incremental differences in output changes were examined, defined as the difference in the distribution of the HbA1c values between both groups over time. Direct program costs and anticipated indirect costs of service utilization were used as cost parameters. A net monetary benefit approach was used to validate cost-effectiveness thresholds via the formation of ICER values. RESULTS: The intervention group had significantly higher reductions in HbA1c-values. Risk stratification of initial HbA1c showed (short-term) cost effectiveness for initially higher HbA1c values. Due to the limited study period, no long-term differences in medical resource utilization could be assessed. CONCLUSION: The GLICEMIA program indicates considerable effectiveness potentials, especially for high-risk patients. The study design seems to have assisted the intervention group's adherence in contrast to the control group. Detailed impacts within the complex intervention could not be validated due to restrictions of the study design as a complex intervention. Overall, statements about effect sustainability and further utilization rates progressions are limited due to a lack of follow-up.
CRIS-Team Scopus Importer:2022-12-23